The Degree of Awareness of Arabic language Female Secondary School Teachers in Jordan about Cyber Security from their Point of View and its Relationship with Some Variables - Ababneh, Eman Abed Al Fattah (Dirasat: Human and Social Sciences, 2022)
Objectives: To identify the degree of awareness of Arabic language female secondary school teachers in Jordan of cyber security from their Point of View and its relationship with the variables of academic qualification, teaching experience, and geographical region. Methodology: The study used the descriptive method. A questionnaire of (30) items was prepared, and the study sample consisted of (330) teachers who were chosen the way stratified random manner from secondary school Arabic language teachers in Jordan in its three Geographical regions (South, Central, and North) in the first semester of the 2021/2022 school year. Results: The degree of awareness was at a high level. Further, there were significant differences at the level (α = 0.05) in the estimates of the study sample due to the academic qualification and in favor of graduate studies. Furthermore, there were no differences at the level (α = 0.05) in their estimates due to the teaching experience and the geographical region. Conclusion: Establishing training centers affiliated to the Jordanian Ministry of Education to train Arabic language teachers to move from the stage of awareness to the stage of application and practice; in order to reduce the increasing number of electronic crimes in Jordan.